Partisipasi Masyarakat Dalam Perencanaan Pembangunan di Desa Makmur Kecamatan Palolo Kabupaten Sigi - Afifah, Nur; Rivai, Abdul; Rapi, Muhammad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
The aim of this research is to describe community participation in development planning in Makmur Village, Palolo District, Sigi Regency. The research method used is a qualitative descriptive research method to provide a clear picture of the problems studied in Makmur Village. Data sources are primary and secondary data, data collection techniques were carried out using observation, interviews and documentation techniques, the informants in this study were 6 people, while the data analysis used was data collection, data condensation, data presentation and drawing conclusions. The research results show that community participation in development planning in Makmur Village, Palolo District, Sigi Regency is still relatively low. Starting from the preparation of the plan, the low level of community participation in participating in the Development Planning Conference was proven based on the attendance list, and at the implementation stage, the community also did not participate because they thought that someone was already employed in the construction. This is also because communication between village officials and the community is not going well and there is a lack of community initiative in providing contributions in the form of personnel in implementing development.